Hypopituitarism manifesting after invasive dental treatment in a patient with carcinoma of the tongue: a case report - Yu Ohashi; Naoko Tsunoda; Kei Onodera; Shin Iijima; Ikuya Miyamoto; Toshimi Chiba; Hiroyuki Yamada (BMC, 2020)
Abstract Background The symptoms of hypopituitarism are not usually discussed in the clinical setting of oral surgery. Case presentation We herein report a case of hypopituitarism that became evident after biopsy and extraction of several teeth in a 68-year-old man with tongue cancer. Three days after biopsy, the patient developed nausea and vomiting, and his serum sodium had fallen to 124 mEq/L. His serum cortisol concentration was low. Although the plasma concentration of adrenocorticotropic hormone (ACTH) was within the normal range, ACTH stimulation testing showed a lack of cortisol response. Given these findings, we suspected secondary adrenal insufficiency. To investigate the cause of secondary adrenal insufficiency, MRI of the head was performed, which revealed pituitary gland atrophy. The results of pituitary anterior lobe hormone-stimulation tests were compatible with hypopituitarism. Thirty days after biopsy, partial tongue resection was successfully performed under general anesthesia with perioperative hydrocortisone supplementation. Conclusions We must be aware of various signs of hypopituitarism when we perform invasive dental treatment.